Application of Hybrid Functions for Solving Duffing-Harmonic Oscillator. (14th August 2014) - Heydari, Mohammad; Loghmani, Ghasem Brid; Hosseini, Seyed Mohammad.; Karbassi, Seyed Mehdi
Abstract : A numerical method for finding the solution of Duffing-harmonic oscillator is proposed. The approach is based on hybrid functions approximation. The properties of hybrid functions that consist of block-pulse and Chebyshev cardinal functions are discussed. The associated operational matrices of integration and product are then utilized to reduce the solution of a strongly nonlinear oscillator to the solution of a system of algebraic equations. The method is easy to implement and computationally very attractive. The results are compared with the exact solution and results from several recently published methods, and the comparisons showed proper accuracy of this method.